Cold Vapor Generation beyond the Input Solar Energy Limit. Issue 8 (3rd May 2018) - Song, Haomin; Liu, Youhai; Liu, Zhejun; Singer, Matthew H.; Li, Chenyu; Cheney, Alec R.; Ji, Dengxin; Zhou, Lyu; Zhang, Nan; Zeng, Xie; Bei, Zongmin; Yu, Zongfu; et al.
Abstract: 100% efficiency is the ultimate goal for all energy harvesting and conversion applications. However, no energy conversion process is reported to reach this ideal limit before. Here, an example with near perfect energy conversion efficiency in the process of solar vapor generation below room temperature is reported. Remarkably, when the operational temperature of the system is below that of the surroundings (i.e., under low density solar illumination), the total vapor generation rate is higher than the upper limit that can be produced by the input solar energy because of extra energy taken from the warmer environment. Experimental results are provided to validate this intriguing strategy under 1 sun illumination. The best measured rate is ≈2.20 kg m −2 h −1 under 1 sun illumination, well beyond its corresponding upper limit of 1.68 kg m −2 h −1 and is even faster than the one reported by other systems under 2 sun illumination. Abstract : A near perfect energy conversion efficiency can be achieved in a solar vapor generation process. When the operational temperature is below that of the surroundings, the vapor generation rate is higher than the upper limit that can be produced by the input solar energy exclusively due to the environmental contribution. The best measured rate is ≈2.20 kg m −2 h −1 under 1 sun illumination.